2005
DOI: 10.17221/6190-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Investigation the effect of abscisic acid on drought stress introduction in wheat seedlings

Abstract: see the full text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The yield index (YI) was suggested by Gavuzzi et al [29], the yield stability index (YSI) was suggested by Bouslama and Schapaugh [30], drought resistance index (DI) was proposed by Lan [31], the yield reduction ratio (YR) was proposed by Golestani-Araghi and Assad [32], the harmonic mean (HM) was proposed by Hossain et al [33], and the golden mean (GOL) was proposed by Moradi et al [34] in order to evaluate the stability of genotypes under both stress and non-stress conditions. The abiotic tolerance index (ATI) and stress susceptibility percentage index (SSPI) were introduced by Moosavi et al [35] for screening drought-tolerant genotypes under stress and non-stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The yield index (YI) was suggested by Gavuzzi et al [29], the yield stability index (YSI) was suggested by Bouslama and Schapaugh [30], drought resistance index (DI) was proposed by Lan [31], the yield reduction ratio (YR) was proposed by Golestani-Araghi and Assad [32], the harmonic mean (HM) was proposed by Hossain et al [33], and the golden mean (GOL) was proposed by Moradi et al [34] in order to evaluate the stability of genotypes under both stress and non-stress conditions. The abiotic tolerance index (ATI) and stress susceptibility percentage index (SSPI) were introduced by Moosavi et al [35] for screening drought-tolerant genotypes under stress and non-stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 12 water stress tolerance indices proposed by several researchers [37][38][39][40][41][42][43][44] were used to evaluate the forage production response (i.e., shoot biomass production) of the nine forage cultivars grown under a high soil water regime (non-stressful conditions) and under middle and low soil water regimes (i.e., moderate and severe water stress). Forage biomass production data recorded for each forage cultivar in each soil water regime were used to calculate water stress tolerance indices.…”
Section: Calculation Of Water Stress Tolerance Indicesmentioning
confidence: 99%